Atomic diffusion in bcc Fe–Mn alloys: Theoretical analysis and experimental measurements across the Curie temperature. (1st June 2023) - Kulitckii, Vladislav; Schneider, Anton; Lukianova, Olga; Wilde, Gerhard; Fu, Chu-Chun; Divinski, Sergiy
Abstract: The influence of a magnetic transition on Fe and Mn diffusion in bcc Fe–Mn alloys as a function of Mn concentration is studied combining experimental measurements and DFT-informed modeling. The radiotracer technique in combination with precise mechanical sectioning or ion-beam sputtering is used to determine the diffusion rates of 59 Fe and 54 Mn in a series of Fe–Mn alloys with up to 1.9 at.%Mn. The solvent and solute enhancement factors are determined. While the diffusion rates of Fe atoms are found to be almost independent on the Mn content in the Fe–Mn alloys in both para- as well ferro-magnetic states, Mn diffusion is strongly enhanced by an increase of Mn concentration in these alloys, especially in the paramagnetic state. The experimental findings are supported by theoretical results, which are analyzed in terms of an equilibrium vacancy concentration, atomic jump frequencies, Mn–vacancy binding energy, short-range ordering tendency and kinetic correlation factors. Graphical abstract: